2022
DOI: 10.1155/2022/5769784
|View full text |Cite
|
Sign up to set email alerts
|

The Conflicting Role of Caffeine Supplementation on Hyperoxia-Induced Injury on the Cerebellar Granular Cell Neurogenesis of Newborn Rats

Abstract: Preterm birth disrupts cerebellar development, which may be mediated by systemic oxidative stress that damages neuronal developmental stages. Impaired cerebellar neurogenesis affects several downstream targets important for cognition, emotion, and speech. In this study, we demonstrate that oxidative stress induced with high oxygen (80%) for three or five postnatal days (P3/P5) could significantly damage neurogenesis and proliferative capacity of granular cell precursor and Purkinje cells in rat pups. Reversal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 118 publications
1
15
0
Order By: Relevance
“…TEM, × 10000 DISCUSSION The current study aimed to examine the prenatal and postnatal effect of thyme co administration with tramadol on the cerebellar granule cells of albino rats. The cerebellar granule cells were chosen as a target of study because their unique maturation from mitotic granule cell precursors (GCPs) to postmitotic GCs, and their radial migration from EGL along to the formation of the IGL (28). LM examination of the developing cerebellum of the control and thyme groups revealed that in gestational day 13, the cerebellum was formed of a primordium that covered by the ventricular zone of the cerebellar.…”
Section: B-experimental Resultsmentioning
confidence: 99%
“…TEM, × 10000 DISCUSSION The current study aimed to examine the prenatal and postnatal effect of thyme co administration with tramadol on the cerebellar granule cells of albino rats. The cerebellar granule cells were chosen as a target of study because their unique maturation from mitotic granule cell precursors (GCPs) to postmitotic GCs, and their radial migration from EGL along to the formation of the IGL (28). LM examination of the developing cerebellum of the control and thyme groups revealed that in gestational day 13, the cerebellum was formed of a primordium that covered by the ventricular zone of the cerebellar.…”
Section: B-experimental Resultsmentioning
confidence: 99%
“…Wistar rats were term-paired (Janvier Labs, Le Genest-Saint-Isle, France) and kept in single cages under standardized conditions (constant 12 h/12 h light-dark cycle, room temperature, 60% relative humidity, and ad libitum to food and water). In all of our animal experiments [ 28 , 43 , 44 , 45 ], newborn pups were kept with a lactating mother for the duration of the experiment. The animal procedures were assessed and approved by the local animal welfare authorities (LAGeSo, approval number G-0145/13 and G-139/18) and complied with institutional guidelines and ARRIVE guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Using an i.p. injection of ketamine (100 mg/kg), xylazine (20 mg/kg), and acepromazine (3 mg/kg), the pups were anaesthetized at P7, P9, P11, and P14 and subsequently transcardially perfused, as previously described [ 28 , 43 , 44 , 45 ]. The entire cerebellar tissue was removed immediately after decapitation and opening of the skull.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations